On some aspects of teaching pop and jazz singing. The significance and the degree of importance of the empirical method for constructing the vocal technique of the students - Paraskov, Iliyan (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Singing, resp. verbal communication, is performed through one instrument – our voice. Messages and emotions are entirely personal and relate to the personality of the performer (the emitter of the message), which requires a variety and uniqueness of models and layouts for creating vocal and verbal specimens. As such, this report focuses on some aspects and issues arising from my work with students in pop and jazz singing. The first and main problem is related to the level of expectations and potentialities of the young performers. The professor should identify the most effective and efficient methodological principles for each specific case. The evolution of pop and jazz music is extremely dynamic, quick, the variety of styles and forms is immense. Therefore, the vocal pedagogue should systematize the most popular and dominant types of vocal and performing techniques in the particular music environment, some of which are outlined in this report. The teacher should determine the level of technical and theoretical preparation that each pupil has. The main problem is to define properly the individual vocal abilities and provide the correct orientation for the student to a suitable style, repertoire and realization as a vocal performer.